Composition, seasonal change, and bathymetry of Ligeia Mare, Titan, derived from its microwave thermal emission. Issue 2 (25th February 2016) - Le Gall, A.; Malaska, M. J.; Lorenz, R. D.; Janssen, M. A.; Tokano, T.; Hayes, A. G.; Mastrogiuseppe, M.; Lunine, J. I.; Veyssière, G.; Encrenaz, P.; Karatekin, O.
Abstract: For the last decade, the passive radiometer incorporated in the Cassini RADAR has recorded the 2.2 cm wavelength thermal emission from Titan's seas. In this paper, we analyze the radiometry observations collected from February 2007 to January 2015 over one of these seas, Ligeia Mare, with the goal of providing constraints on its composition, bathymetry, and dynamics. In light of the depth profile obtained by Mastrogiuseppe et al. (2014) and of a two‐layer model, we find that the dielectric constant of the sea liquid is <1.8, and its loss tangent is < 3.6 − 2.1 + 4.3 × 10 − 5 . Both results point to a composition dominated by liquid methane rather than ethane. A high methane concentration suggests that Ligeia Mare is primarily fed by methane‐rich precipitation and/or ethane has been removed from it (e.g., by crustal interaction). Our result on the dielectric constant of the seafloor is less constraining < 2.9 − 0.9 + 0.9, but we favor a scenario where the floor of Ligeia Mare is covered by a sludge of compacted and possibly nitrile‐rich organic material formed by the deposition of photochemical haze or by rain washing of the nearby shores. We use these results to produce a low‐resolution bathymetry map of the sea. We also estimate the temperature variation of the bulk sea between February 2007 and July 2013 to be <2 K, which provides a constraint on its net evaporative cooling currently being explored in ocean circulation models. Lastly, we suggest a lag in the summer warming of the northern polar terrains. Key Points: Radiometry observations of Ligeia Mare support a liquid composition dominated by methane The seafloor of Ligeia Mare probably consists of a sludge of compacted organic‐rich material No significant net cooling from 2007 to 2013 but possible lag in the summer warming in the north